Regulatory and Economic Challenges in Contemporary Crowdfunding-Based Cash Waqf - Suhairi, Suhairi; Saputra, Afriyan Arya; Alimuddin, Agus; Mutsalim Khareng (MILRev: Metro Islamic Law Review, 2025)
Cash waqf is an Islamic financial instrument that has the potential to fund social projects, particularly in addressing inequality and poverty issues. However, the traditional management still faces challenges, such as limited transparency and public participation reach. Digitization through fintech with crowdfunding modeling was considered capable of increasing donor participation while improving the effectiveness of management and distribution. This research aimed to provide a comprehensive overview of the development of cash waqf, mapping the trends, identifying the main factors influencing its development, and exploring gaps, particularly in the context of integration with crowdfunding models. The process led to the adoption of performance analysis and science mapping methods. Performance analysis was conducted descriptively to measure productivity and impact through bibliometric indicators. Science mapping was used to review the research landscape by analyzing the relationships and structures of topics, authors, and relevant institutions. It was also used to identify collaboration patterns, thematic focuses, including under-researched areas, and integration with crowdfunding platforms. The results showed that regulatory aspects, contemporary digital technology innovations, and the role of Islamic financial institutions were factors influencing the development of cash waqf research. Topic modeling analysis proved that the exploration on the integration of cash waqf and crowdfunding was limited. This led to a gap in research on the governance of digital waqf platforms, as well as strategies to enhance public participation through technology. The research provided a map that served as a reference, including used by regulators and platform developers in designing policies and innovations for digital waqf products.